4x-2(x-3)=x+12

Simple and best practice solution for 4x-2(x-3)=x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2(x-3)=x+12 equation:


4x-2(x-3)=x+12

We simplify the equation to the form, which is simple to understand
4x-2(x-3)=x+12

Reorder the terms in parentheses
4x+(-2x+6)=x+12

Remove unnecessary parentheses
+4x-2x+6=+x+12

We move all terms containing x to the left and all other terms to the right.
+4x-2x-1x=+12-6

We simplify left and right side of the equation.
+1x=+6

We divide both sides of the equation by 1 to get x.
x=6

See similar equations:

| 7(p+2)-4p=3p+14 | | 100y+300x*40=8400 | | 7/9*1/5*3/35 | | -1/6-6 | | -2/9*-1/4 | | [3+4x]=15 | | 100+300*40=8400 | | 21/1575 | | 2(v-3)-7=-3(-5v+1)-5u | | C/6=4 | | -4(-5w+6)-7w=5(w-5)-9 | | 2n+10=107.50 | | (-2/4)x+3=1 | | 142+2.7x=300 | | 7(n-2)-6=2n+8+n | | 900x=10 | | 2(x-.5)-6x= | | 142+2.7x=40 | | x+5-8=-2 | | -5(2w-6)+w=3(w+8) | | 3000x-6000(x+0.3)=93 | | 1=(-w+6) | | w(4-w^2)=8-w^2 | | [x-8]=11 | | 7(u+2)=42 | | 18x+4/17-17x=1/3 | | -3x-2(8+5x)=14-5(2x-5) | | 6(x+3)-10=-2(x-4) | | x+(-12)=13 | | -2(4n+4)=10 | | 3(13u-81)=21 | | x^4/y^5*y^4/x |

Equations solver categories